Dental and medical students’ self-directed learning and motivation: An evaluation of two multiple-choice questions systems using machine learning - Leth Rasmussen, Emilie; Have Musaeus, Malthe; Dahl, Mads Ronald; Løvschall, Henrik; Musaeus, Peter (Tidsskriftet Læring og Medier (LOM), 2024)
This comparative case study reports a study investigating student evaluation of Multiple-Choice questions (MCQ) through machine learning as a means of learning. The focus is on self-directed learning and motivation. The study evaluates two systems developed at Aarhus University: "MED MCQ" used by medical students, and "MCQ anatomy" used by dental students. The study evaluates two surveys in SurveyXact with responses from 126 medical students and 70 dental students. We use topic modeling over free text responses. The machine learning model identifies two groups of students who, in different ways, experience interacting with the system as motivating and facilitating their learning process. The students' experience increases self-directed learning by being able to choose the form of presentation of questions and answer questions independently of the instructor. The article discusses how educators and developers can use MCQs to promote student learning and how to analyze open-ended questions with machine learning.